Prevention And Decreasing Stunting: Implementing Policies In Subdistrict Wori, North Minahasa District - Dumanauw, Patricia Anggi; Bulo, Laurens L; Tarore, Steven (International Journal of Information Technology and Education, 2025)
This study evaluates the implementation of stunting prevention and reduction policies in Wori District, North Minahasa Regency, based on Regent Regulation Number 23 of 2023 concerning Integrated Stunting Prevention and Reduction. Although North Minahasa Regency shows a downward trend in stunting rates, Wori District recorded an increase in cases of up to 43 children in February 2025. The study used a descriptive qualitative approach with a phenomenological method, involving observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman (2014) model through the stages of collection, condensation, presentation, and conclusion, along with verification. The results of the study showed that although the programs (Posyandu, PMT, nutrition education, specific and sensitive interventions, and involvement of Human Development Cadres) had been implemented, their implementation had not been optimal due to limited Village Fund budget, low capacity and number of cadres, socio-cultural barriers, inadequate sanitation infrastructure, and cross-sectoral coordination that was not yet synergistic. Based on the theories of Edward III, Van Meter & Van Horn, and Mazmanian & Sabatier, the determinant factors are mainly located in the context of implementation, such as the capacity of implementers, local political support, and community participation. Recommendations include increasing budget allocation, strengthening human resource capacity (continuous training for nutrition cadres and KPM), and strengthening cross-sector convergence coordination so that specific and sensitive interventions run in an integrated manner.